Impact of climate change to sedimentation processes and microplastics gradients: a case study in a semi-closed deep ocean system, Lemnos basin, Greece - Kousidou, Georgia; Tsabaris, Christos; Pappa, Filothei; Androulakaki, Effrosyni; Korres, Gerasimos; Krassakopoulou, Evangelia (HNPS Advances in Nuclear Physics, 2025)
The marine environment has undergone substantial changes in recent decades, due to by-products that cause pollution and end up to the marine systems mainly from the coastal zone and the drainage basins. The purpose of this work is to study environmental changes and contamination during the last century, taking into account sediment analysis as the final recipient of discharged matter at a semi-closed marine system. From the basin of Lemnos, at a depth of 1550 m, two sediment cores were sampled and analyzed, by applying gamma-ray spectrometry for radionuclides measurement and density separation/microscopic inspection for microplastic particles determination. The sedimentation rate was determined using the vertical profiles of 210Pbex methods and validated via 137Cs measurements. The ratio of 226Ra/228Ra activity concentrations was less than unity demonstrating that the main mechanism that takes place in terms of sediment dynamics is accumulation/accretion process. The microplastic particles’ concentrations were measured and correlated with the increased water supply of the rivers flowing into the North Aegean, combined by the production of dense water masses. The data were also interpretred according to the impacts of climate change.such as the increase of the seawater surface temperature, the increase of the frequency of deep water formation and the increase of the sedimentation rate during the last ecades due to extreme weather events.